2024
DOI: 10.1111/dom.15529
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon‐like peptide‐1 receptor agonists modestly reduced blood pressure among patients with and without diabetes mellitus: A meta‐analysis and meta‐regression

Frederick Berro Rivera,
Grace Nooriza O. Lumbang,
Danielle Rose Magno Gaid
et al.

Abstract: AimThe cardiovascular benefits provided by glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) extend beyond weight reduction and glycaemic control. One possible mechanism may relate to blood pressure (BP) reduction. We aim to quantify the BP‐lowering effects of GLP1‐RAs.MethodsA comprehensive database search for placebo‐controlled randomized controlled trials on GLP‐1RA treatment was conducted until December 2023. Data extraction and quality assessment were carried out, employing a robust statistical analysi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 100 publications
(327 reference statements)
0
5
0
Order By: Relevance
“…The odds reduction in MACE with GLP-1 RAs do not significantly differ between those with BMI<30 or BMI>30. The protective effect of GLP-1 can be due to its direct effect in GLP-1 receptors in the heart, independent of its ability to decrease body weight [ 32 ] and improve lipid metabolism which are acted upon by GLP-1 receptors in the brain and adipose tissues [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The odds reduction in MACE with GLP-1 RAs do not significantly differ between those with BMI<30 or BMI>30. The protective effect of GLP-1 can be due to its direct effect in GLP-1 receptors in the heart, independent of its ability to decrease body weight [ 32 ] and improve lipid metabolism which are acted upon by GLP-1 receptors in the brain and adipose tissues [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…GLP-1 receptor agonists also induce modest (2-4 beats/min) tachycardia, irrespective of the presence of hypertension. These effects of GLP-1 receptor agonists on blood pressure are supported by Rivera et al, 4 who performed a systematic review and meta-analysis of randomized controlled trials relating to the effects of four GLP-1 receptor agonists, semaglutide subcutaneously, exenatide once weekly, liraglutide and dulaglutide, on blood pressure in both type 2 diabetes and obesity without type 2 diabetes. 4 Not surprisingly, Rivera et al report marked inconsistencies in the design and duration of these studies; moreover, 31 of 63 related to liraglutide.…”
mentioning
confidence: 81%
“…These effects of GLP-1 receptor agonists on blood pressure are supported by Rivera et al, 4 who performed a systematic review and meta-analysis of randomized controlled trials relating to the effects of four GLP-1 receptor agonists, semaglutide subcutaneously, exenatide once weekly, liraglutide and dulaglutide, on blood pressure in both type 2 diabetes and obesity without type 2 diabetes. 4 Not surprisingly, Rivera et al report marked inconsistencies in the design and duration of these studies; moreover, 31 of 63 related to liraglutide. While a previous analysis suggested that blood pressure reduction did not contribute to the cardiovascular benefits observed in LEADER, 1 this issue remains contentious.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…It has long been observed that tight glycemic control can worsen diabetic retinopathy in the short term in some; however, this is outweighed by the long-term systemic benefits . Of note, only a modest lowering of systolic blood pressure has been noted with GLP-1 RAs use …”
mentioning
confidence: 99%